The evaluation of treatment of chronic catarrhal gingivitis on a background of iron deficiency anemia - Басіста, Анастасія Степанівна; Рожко, Віталій Іванович (Actual Dentistry, 2018)
Abstract. The course of inflammatory periodontal diseases is substantially complicated by iron deficiency anemia, and dental treatment becomes practically unpromising. The aim of the study was to evaluate treatment of chronic catarrhal gingivitis on the background of iron deficiency anemia. The study involved 94 patients 22–45-years old. For evaluation of periodontal status we determined the OHI-S, РМA, CPITN indexes. The effectiveness of periodontal treatment was determined by the results of visual and instrumental gums assessment, periodontal indexes and radiological assessment of alveolar bone. Stable remission in patients with iron deficiency anemia is only possible after complex hematologic treatment with iron and supportive periodontal therapy. Key words: periodontium, hygiene, tooth debris, bleeding, catarrhal gingivitis, iron deficiency anemia, treatment.